2010
DOI: 10.1084/jem.20100209
|View full text |Cite
|
Sign up to set email alerts
|

IL-2 reverses established type 1 diabetes in NOD mice by a local effect on pancreatic regulatory T cells

Abstract: Regulatory T cells (T reg cells) play a major role in controlling the pathogenic autoimmune process in type 1 diabetes (T1D). Interleukin 2 (IL-2), a cytokine which promotes T reg cell survival and function, may thus have therapeutic efficacy in T1D. We show that 5 d of low-dose IL-2 administration starting at the time of T1D onset can reverse established disease in NOD (nonobese diabetic) mice, with long-lasting effects. Low-dose IL-2 increases the number of T reg cells in the pancreas and induces expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
348
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(380 citation statements)
references
References 30 publications
26
348
1
5
Order By: Relevance
“…Indeed, decreased Foxp3 expression in the periphery causes defective suppressive function of Treg cells and their conversion into effector cells, which contribute to, rather than inhibit, autoimmune diseases [26,27,29]. Recent data suggest strongly that IL-2 may play a role in the maintenance of peripheral Treg-cell suppressive capacities by promoting sustained expression of Foxp3 [18,30,31]. In the present article, we show that continuous interactions with self are required for maintaining Treg-cell suppressive function in the periphery.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Indeed, decreased Foxp3 expression in the periphery causes defective suppressive function of Treg cells and their conversion into effector cells, which contribute to, rather than inhibit, autoimmune diseases [26,27,29]. Recent data suggest strongly that IL-2 may play a role in the maintenance of peripheral Treg-cell suppressive capacities by promoting sustained expression of Foxp3 [18,30,31]. In the present article, we show that continuous interactions with self are required for maintaining Treg-cell suppressive function in the periphery.…”
Section: Discussionsupporting
confidence: 52%
“…Then, Foxp3 expression is considered as sufficient to maintain natural Tregcell suppressive function in the periphery. Recent data suggest that IL-2 is important to stabilize Foxp3 expression in peripheral Treg cells [18,30,31]. Our study places on firm ground the importance of continuous interactions with self in maintaining Treg-cell suppressive capacities in the periphery.…”
supporting
confidence: 60%
“…Consequently, whereas heterozygous NOD mice expressing one copy of each B6 and NOD Il2 alleles (collectively encoding superior IL-2 production capacity versus wild-type NOD mice) harbor FoxP3 + CD4 + CD25 + Treg cells with increased anti-diabetogenic function, Il2-hemizygous NOD mice carrying one copy of a genetargeted NOD Il2 allele develop an accelerated form of diabetes that is associated with impaired FoxP3 + CD4 + CD25 + Treg-cell development, recruitment, and function [13]. In agreement with these observations, administration of low-dose IL-2 protects NOD mice from diabetes [14][15][16] and neutralization of IL-2 accelerates disease [17]. Furthermore, Il2RA, encoding the IL-2 receptor α chain (IL-2Rα; CD25) is strongly associated with human T1D [18] and human Il2RA-linked T1D susceptibility segregates with an approximately 30-50% decrease in the expression of CD25 premRNA and surface protein on activated/memory T cells and, to a lesser extent, Treg cells [19].…”
mentioning
confidence: 65%
“…In pre-clinical studies, Tang et al observed that IL-2/anti-IL-2 complexes could "repair" Tregs within the pancreas and alter the progression of the disease [34]. Strikingly, Grinberg-Bleyer et al found that IL-2 reverses established diabetes in NOD mice by a local effect on pancreatic regulatory T cells [43]. Tang et al showed that infusion of Tregs into NOD mice prevents disease onset and even reverses diabetes in mice with hyperglycemia [44].…”
Section: Treg Overview and Role In Dmmentioning
confidence: 99%